Analysis of the Role and Strategies of Public Speaking in Building Self-Confidence - Sari, Ratna; Indra, Syaiful; Andriyani, Juli (An-Nadwah, 2024)
The low proficiency in public speaking among students is not a trivial issue, as public speaking significantly influences the enhancement of students' self-confidence when speaking in public. This skill is not only relevant in the educational context but is also crucial in the professional world. The aim of this study is to analyze the role and strategies of public speaking in developing the self-confidence of engineering students at Kolej Vokasional Nibong Tebal, Pulai Pinang. The research method employed is qualitative, utilizing data collection techniques such as observation, in-depth interviews, and documentation. The data analysis technique used is descriptive analysis following the Miles and Huberman model. The results indicate that factors contributing to the low public speaking proficiency and self-confidence among engineering students at Kolej Vokasional Nibong Tebal, Pulai Pinang, include the lack of formal training in public speaking, limited opportunities for practice in real situations, insufficient foundational knowledge of public speaking techniques, high levels of anxiety and fear when speaking in public, lack of environmental support, challenges in using the medium of instruction, and previous negative experiences. Public speaking plays a crucial role in building self-confidence through the enhancement of self-efficacy, anxiety management, as well as social support and positive feedback. To improve public speaking and develop self-confidence among engineering students at Kolej Vokasional Nibong Tebal, a directed and effective strategy is required. This includes integrating public speaking into the curriculum, organizing workshops and intensive training, encouraging participation in practical activities, and providing mentoring and coaching programs.